Niche news the politics of news choice - Stroud, Natalie Jomini (New York ; Oxford : Oxford University Press, 2011)
Fox News, MSNBC, The New York Times, The Wall Street Journal The Rush Limbaugh Show, National Public Radio - with so many options, where do people turn for news? This book examines the extent to which our political leanings guide our news selections and whether likeminded news use is democratically consequential.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Mass media -- United States -- Audiences; Mass media and public opinion -- United States; Press and politics -- United States; Television broadcasting of news -- United States; Radio journalism -- United States